External Stakeholder’s Perspective on Local Government’s Performance Information (A Study of Administrative Information in Wajo Regency) - Nawir, Muhammad Achyar (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2018)
This study explored the relationship between the local government and the external stakeholders in the frame of the administrative performance information publication. The research findings show that poor practices of administration and the lack of social activism have kept the information asymmetry and goal conflict in existent. In addition, instead of making effort to overcome information asymmetry and goal conflict, the stakeholders preferred to exit the relationship. This is an exploratory single case study in the context of Wajo, a locale area with a long history of a moral system and democratic practices since the fifteenth century.